Waramopoy dan Kelentangan Dalam Upacara Kwangkay Pada Suku Dayak Benuaq di Kalimantan Timur - Asti Hamdani (Institut Seni Indonesia Yogyakarta, 2017)
Kwangkay is one of the most recent death ceremonies of all the processes of death ritual that found in the Dayak Benuaq, East Kalimantan. This ceremony is doing by digging back the ancestral bones of the deceased and has been buried for 4 years or more. The bones are led by pengewara (traditional leader). Wara Mopoy is a vocal art form of a mantra recited by the rulers during the routine ritual of giving food to the spirits of the ancestors in every day and it is believed to be the medium to deliver the soul to the highest cosmos (Lamut Paradise). During the ritual process, there is also a musical opposition that serves as a dance accompaniment Ngerangkaw( the dance that carried bones in the back).Death becomes something that passes by certain rules and ritual levels because they believe that the nature of the paradise has different levels according to the level of ceremony performed by the living (family and relatives). This kwangkay ceremony is closely related to the origins and mythology of the Dayak tribe of Benuaq that has shaped and bound them in a Benuaq customary and customary order. Implementation was through a variety of requirements, stages, and complicated process to take 21 days. Keywords: kwangkay, wara mopoy, kelentangan.